(untitled) (KYAMC Journal, 2019)
Background: To determine the most common position of both mental foramen in selected Bangladeshi population. Materials and Methods: This was a cross sectional study. Convenient sampling technique was used. For this seventy five panoramic radiographs of Bangladeshi population were taken from Out Patient Department of MH Samorita dental unit, Dhaka, Bangladesh. Result: The most common Horizontal position of the mental foramen was in line with second premolar (position 4). In vertical axis, the location of MF in lower half of body of mandible was found in all OPGs (100%). Conclusion: The knowledge about the position of the mental foramen may be helpful to the dental surgeons to achieve full anesthesia after nerve block. KYAMC Journal Vol. 10, No.-1, April 2019, Page 31-34